Left, right, up and downstage: Leaves and lateral roots histological trait prospection for drought tolerance in commercial Coffea arabica cultivars - Godinho, Natália de Oliveira (2025)
The climate change and water deficit challenges plant producers all over the world, and have consequences to coffee production and quality. In this research we have approached anatomical traits from vegetative organs of 13 Coffea arabica genotypes, selected based on their contrasting behavior to water deficit. Leaf blade, petiole and primary root cross sections were evaluated, and the epidermal, fundamental, and vascular tissues descriptive anatomy, histometric and histochemistry examined. Despite all plants were in the same environment (CEPC/EPAMIG, Patrocínio, MG, Brazil), there were differences among the genotypes and groups of more tolerant and more susceptible accesses. Petiole cross section, vascular tissue and phloem and cambium; and percentage of stele, pericycle and phloem and cambium in primary roots exhibited differences among the contrasting genotypes, highlighting an inborn association of vascular tissue and other features with water deficit resistance. This association was observed in the mild to medium correlations among vascular tissue, epidermis, phloem and cambium in roots and petioles. Possible relation of qualitative traits such as the lignification of root epidermis, lipidic substances in outer cortical cell layers, and area/number of cell layers in the cortex are approached as possible traits in the seek for water deficit tolerance in C. arabica.